APLIKASI KEAMANAN E-MAIL MENGGUNAKAN ALGORITMA AES (ADVANCED ENCRYPTIO STANDARD) BERBASIS ANDROID - Nur Ayun Qolbu; Sutardi Sutardi; LM. Tajidun (Informatics Engineering Department of Halu Oleo University, 2016)
The e-mail is one of the facilities provided by the android based mobile phone so that increasingly changing the way people communicate. First long distance communication is still using the conventional manner, that is by sending each other letters, but now remote communication can be done easily and quickly. But with so many new technologies are evolving, there are many who disseminated information is both public and private, or secret, so that information security is not guaranteed. E-mail security applications needed to secure the information by applying the science of cryptography algorithm AES (Advanced Encryption Standard). AES algorithm is a cryptographic algorithm that is sufficiently robust security and easy to solve and apply. In this application is implemented using the Java programming language, android studio. The test files used in the e-mail application is txt, docx, pdf and ppt. The results of this study states algorithm AES (Advanced Encryption Standard) can be implemented into the process of encryption and decryption at the application of e-mail security. This can ensure that the parties understand the message or file is sent via e-mail is the right side. Keywords— AES (Advanced Encryption Standard) Algorithms, E-mail Security, Android.